Faktor risiko penyakit jantung koronari di kalangan wanita yang dimasukkan ke wad UKM - Ahmad Shahrir H.R.,; Ali S.,; George E.,; Koh B.B.,; Md. Zamri A.R.,; Norlelawati A.T.,; Norliza Z.,; Thirugnana SS, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1994)
A case control study was done to determine the relationship between Coronary Heart Disease (CHD) in women and hypertension, diabetes mellitus, smoking and a positive family history of CHD. Forty case of CHD from UKM medical ward and 40 control from UKM Orthopaedic and Surgical wards were taken. The majority of patients were Malays (50%), Chinese and Indians were 25% each. This study showed a significant relationship between CHD and hipertension (p<0.05), diabetes mellitus (p<0.05) and a positive family history of CHD (p<0.05). However we were unable to demonstrate a significant relationship between CHD and smoking (p>0.05).